Synthesis and Anti-Inflammatory Activity of New Nicotinoyl Amides - O.A. Nurkenov; S.D. Fazylov; Zh.S. Nurmaganbetov; T.M. Seilkhanov; A.Zh. Mendibayeva; S.K. Kabieva; E.M. Satbaeva (Eurasian Chemico-Technological Journal)
The article presents the results of a study of the amination reaction of nicotinic acid chlorohydride with amines morpholine, cytisine, and 1-aminoadamantane, which are often used in the search and creation of drugs for respiratory and circulatory stimulants. The study was conducted to search for new biologically active compounds with anti-inflammatory activity. The synthesis of new aminoamides was carried out by the interaction of nicotinic acid with molecules of morpholine, cytisine, and adamantane in anhydrous ethanol. As a result of the conducted studies, new amides of nicotinic acid with high yields (90.7–93.1%) were obtained. The structures of the new compounds were determined using NMR 1H and 13C spectroscopy methods, as well as data from two-dimensional spectra of COSY (1H-1H), HMQC (1H-13C), HMBC (1H-13C) and mass spectrometry. The results of an experimental study of the anti-inflammatory activity of synthesized new amides are presented. The anti-inflammatory effect of nicotinic acid N-adamantylamide was established, other new amides were ineffective compared with ibuprofen (p2 < 0.05).